Superficial basal cell carcinoma on the face is a diagnostic challenge - Joydeep Singha; Naval Patel (Wolters Kluwer Medknow Publications, 2016)
Basal cell carcinoma (BCC) is the most common non-melanoma skin cancer. The incidence of BCC is rising. The nodular, superficial spreading, and infiltrating variants are the three most commonly encountered types of BCC in descending order of prevalence. Superficial spreading basal cell carcinoma (SSBCC) accounts for 15-26% of all cases of BCC. It usually occurs on the trunk and upper extremities, but may be seen on the face. Surgical excision is the most commonly used treatment for BCC. Topical chemotherapy agents such as imiquimod or 5-fluorouracil (5-FU) may be various alternatives or adjuvants in the treatment of SSBCC. characteristically shows areas of uninvolved skin between tumor nests.[7]